(3JMGdaGJ GdYhdeI GdYScQjI hGdbGfhf GdOhdj (B/s - (3CHh GdNjQf, GdSjO eUWai CMeOs ((3GdbGgQI(B: s (3GjJQGc(B, s, 2005)
(3GdJMGda GdOhdj aj MQH GdNdjL GdKGfjI(B: (3GdJcSja GdbGfhfj dZRh GdYQGb ddchjJ, OhQ GdCee GdeJMOI aj MQH GdNdjL GdKGfjI, GdWHjYI GdbGfhfjI ddJMGda GdOhdj aj MQH GdNdjL GdKGfjI, GdeSDhdjI GdOhdjI Yf MQH GdNdjL GdKGfjI GdJMGda GdOhdj VO GaZfSJGf aj VhA CMcGe GdbGfhf GdOhdj GdYGe(B: (3GdMQH VO GaZfSJGf aj VhA CMcGe GdbGfhf GdOhdj GdYGe, GdMeGjI GdbGfhfjI ddWjQGf GdeOfj aj GdbGfhf GdOhdj, GdBKGQ GdeJQJHI Ydi GdMQH VO GaZfSJGf aj VhA GdbGfhf GdOhdj MQH GdNdjL GdKGdKI aj VhA GdbGfhf GdOhdj GdeYGUQ(B: (3OhQ GdCee GdeJMOI aj MQH GdNdjL GdKGdKI, GdGfJgGcGJ GdJj GQJcHJgG bhGJ GdJMGda CKfGA MQH GdNdjL GdKGdKI, GdeSDhdjI GdOhdjI Yf MQH GdNdjL GdKGdKI(B.s
(3GdeQGLY U(B.351s
Keywords: (3GdJONdGJ GdCLfHjIs; (3GdYdGbGJ GdOhdjIs; (3GdbGfhf GdOhdjs; (3JShjI GdfRGYGJs; (3MQH GdNdjL (B1991s